Basic structures of reality essays in meta-physics - McGinn, Colin, 1950- (New York : Oxford University Press, 2011)
In 'Basic Structures of Reality', Colin McGinn deals with questions of metaphysics, epistemology, and philosophy of mind from the vantage point of physics.
Also issued in print format.
Description based on online resource; title from PDF title page (viewed on Jan. 20, 2012).
Includes index.
Keywords: Physics -- Philosophy; Metaphysics